The effect of trait mindfulness on social media rumination: Upward social comparison as a moderated mediator - Gu, Chenyu; Liu, Shiyu; Chen, Subai (Frontiers in Psychology, 2022)
Social media rumination – the tendency to repetitively think about one’s social media posts, related situational factors, and consequences of those posts – is a salient reason explaining why social media use is linked to negative mental health and interpersonal outcomes among individuals. Mindfulness, which involves paying attention, on purpose, and nonjudgmentally, is antithetical in nature to rumination and appears effective in reducing rumination. However, in the context of social media, the nature of the relationships between rumination and mindfulness has gained few attentions. Current research indicates that both mindfulness, upward social comparison (USC), and self-esteem are implicated in social media rumination (SMR), yet no research has synthesized these findings into one model. Therefore, this study aims to explore the relationship between mindfulness and SMR, the mediating effect of USC, and the moderating effect of self-esteem. Mplus and PROCESS macro for SPSS with bootstrapping were used to test the model. Results showed that USC plays a moderated mediator role in the relationship between mindfulness and SMR. Specifically, high mindfulness individuals do not necessarily have less USC. Self-esteem moderated the above mediation. This research provides a deep explanation for the beneficial effect of mindfulness on social media rumination.